A minicircuitry of microRNA‐9‐1 and RUNX1‐RUNX1T1 contributes to leukemogenesis in t(8;21) acute myeloid leukemia. Issue 3 (10th November 2016) - Fu, Lin; Shi, Jinlong; Liu, Anqi; Zhou, Lei; Jiang, Mengmeng; Fu, Huaping; Xu, Keman; Li, Dandan; Deng, Ailing; Zhang, Qingyi; Pang, Yifan; Guo, Yujie; et al.
Abstract : MicroRNA‐9‐1( miR‐9‐1 ) plays an important role in the mechanism that regulates the lineage fate of differentiating hematopoietic cells. Recent studies have shown that miR‐9‐1 is downregulated in t (8; 21) AML. However, the pathogenic mechanisms underlying miR‐9‐1 downregulation and the RUNX1‐RUNX1T1 fusion protein, generated from the translocation of t (8; 21) in AML, remain unclear. RUNX1‐RUNX1T1 can induce leukemogenesis through resides in and functions as a stable RUNX1‐RUNX1T1 ‐containing transcription factor complex. In this study, we demonstrate that miR‐9‐1 expression increases significantly after the treatment of RUNX1‐RUNX1T1 (+) AML cell lines with decitabine (a DNMT inhibitor) and trichostatin A (an HDAC inhibitor). In addition, we show that RUNX1‐RUNX1T1 triggers the heterochromatic silencing of miR‐9‐1 by binding to RUNX1‐binding sites in the promoter region of miR‐9‐1 and recruiting chromatin‐remodeling enzymes, DNMTs, and HDACs, contributing to hypermethylation of miR‐9‐1 in t (8; 21) AML. Furthermore, because RUNX1, RUNX1T1, and RUNX1‐RUNX1T1 are all regulated by miR‐9‐1, the silencing of miR‐9‐1 enhances the oncogenic activity of these genes. Besides, overexpression of miR‐9‐1 induces differentiation and inhibits proliferation in t (8; 21) AML cell lines. In conclusion, our results indicate a feedback circuitry involving miR‐9‐1 and RUNX1‐RUNX1T1, contributing to leukemogenesis in RUNX1‐RUNX1T1 (+) AML cell lines. Abstract : What's new? T (8;21), which is one of the most frequent chromosomal translocations in acute myeloid leukemia (AML), leads to the formation of the RUNX1‐RUNX1T1 fusion transcription factor. The mechanisms underlying leukemogenesis however remain unclear. Here, the authors show that RUNX1‐RUNX1T1 triggers the heterochromatic silencing of miR‐9–1, contributing to hypermethylation of miR‐9–1 promoter in t (8; 21) AML. miR‐9–1 silencing promotes the expression of target genes, including RUNX1, RUNX1T1 and RUNX1‐RUNX1T1, which prevents differentiation and promotes proliferation of t (8; 21) AML. The results indicate a feedback circuitry involving miR‐9–1 and RUNX1‐RUNX1T1 contributing to leukemogenesis in t (8; 21) AML cell lines.